Let your mind run : a memoir of thinking my way to victory - Kastor, Deena (Crown Archetype, 2018)
"From an Olympic medalist runner and the record-holder in the women's marathon and half-marathon, a lyrical, inspirational memoir on how harnessing the power of the mind can unlock hidden potential Deena Kastor was a star youth runner with tremendous promise, yet her career almost ended after college. Her competitive method--run as hard as possible, all the time--brought her to the brink of burnout and fostered a frustration and negativity that threatened to obscure her success. On the verge of quitting, she took a chance and moved to the high altitudes of Alamosa, Colorado, where legendary coach Joe Vigil had started the first professional distance-running team. There she encountered what would become the dominant theme in her running career: the idea that building an elite runner meant developing the mind. Every gain in physical fitness would be dependent on and compounded by gains in mental fitness, which in turn depended on developing a mind-set that could marshal powerful forces of belief and confidence capable of conquering negativity in all its forms. Building a mind so strong would be a decade-long project, but it would propel Kastor to the pinnacle of running--to American records in every distance from the 5K to the marathon, and to America's first Olympic medal in the marathon in twenty years. Let Your Mind Run is a granular look inside the mind of an elite athlete, a remarkable story of achievement, and a fascinating primer on how the small steps of cultivating positivity can lead to outsize gains in performance"--